An Analysis Of English - Indonesian Translation Of Wise Words Used In Hidup Sejahtera Selamanya, Kaya Raya Selamanya, And Dengan Hati Menuju Tempat Tertinggi By Gede Prama - Kustanti, Mustariyah Lisa (2004)
This research paper focused on describing addition and omission in wise words translation by Gede Prama. Besides, the researcher explains the accuracy of the translation. For analyzing the data, the researcher uses qualitative descriptive method, because the research is going to describe of her finding. The data are all wise words taken from the three book of Gede Prama entitled Hidup Sejahtera Selamanya, Kaya Raya Selamanya, and Dengan Hati Menuju Tempat Tertinggi. In conducting this study, the writer collected the data first and then classified them dealing with its addition and omission. After classifying the data, the researcher analyzed the data one by one based on the accuracy of translation. Based on the data analysis, the result of this research are 9 data including in word addition, 6 data are phrase addition, 3 data are clause addition, 7 data are word omission, 4 data are phrase omission, and 2 data are clause omission. Meanwhile, on its accuracy there are 32 data are accurate and 11 data are inaccurate. Finally, the researcher concludes that this translation is accurate because 74,4% from 43 data are accurate and only 24,6% are inaccurate.